Study the effect of adding Cuminum cyminum seeds in the diet on semen characteristics and hormones level in serum of local bucks - Zalzala, Sadeq jaafer (The Iraqi Journal of Veterinary Medicine, 2017)
This study was conducted on sixteen local Iraqi bucks aged 3 to 4 in College of Veterinary Medicine/ University of Baghdad from January to May, 2016. They were divided randomly into two equal groups; 1st group (G1) was treated by oral administration of 15 gm/daily cumin seeds for 3 weeks, while the 2nd group (G2) represented control group. The 1st group showed a significant (P≤0.05) increased in semen volume (2.08±0.36 ml), furthermore number of sperm was increased significantly also according to assessment of semen color (4.23±0.26). Mass and individual motility showed significant higher level in the 1st group (86.00±1.97, 87.00±1.62%, respectively), than in the control group. Significant increased in cortisol and testosterone level recorded in the 1st group as compared with the 2nd group. In conclusion, cumin seeds enhanced improvement of semen bucks quality.